A bimodal soft electronic skin for tactile and touchless interaction in real time - Jin Ge (Nature Portfolio, 2019)
To realize electronic skins for emerging technologies that require multifunctional sensing capability, intelligent design strategies are needed. Here, the authors report electronic skins with a single sensory unit that simultaneously transduces both tactile and touchless stimulations.